EFEK ANALGETIK ANTIPIRETIK EKSTRAK ETANOL KULIT BUAH MANGGIS (Garcinia mangostana L.) PADA TIKUS PUTIH JANTAN GALUR WISTAR - Ika Puspitaningrum; Lia Kusmita; Wahyuning Setyani (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2014)
ABSTRACT Antipyretic analgesic is a compound that can relieve pain and can reduce fever. One of the plants that has potential as antipyretic analgesic is mangosteen (Garcinia mangostana L.). Mangosteen peel contains flavonoids and alkaloids that may have an effect as an analgesic. In addition, flavonoids could inhibit prostaglandin that has antipyretic effect. This study aims to determine the antipyretic analgesic effect of ethanol extract of mangosteen peel and the effective dose.             Analgesic and antipyretic test using 25 male Wistar rats were divided 5 groups , I (negative control) CMC Na 0,5 % , II (positive control) paracetamol 50 mg/kg body weight, and III, IV and V suspension of the ethanol extract of the skin manggis 50; 100 and 200 mg/kg body weight. Pain stimuli by dipping a rat tail in the water temperature of 40° C for 10 seconds. Rat response to a painful stimulus done prior to treatment (normal response), and 30 minutes after treatment. While excitatory fever in rat by injection of 0.2 ml vaccine DPT are intramuscular. Rectal temperature of rat were measured before treatment (initial temperature), 60 minutes after the vaccine, as well as 30 minutes after treatment . Rat response to a painful stimulus and a rectal temperature of rat was analyzed using SPSS statistical release 16 .            The results showed that the ethanol extract of mangosteen peel can improve the rat response to pain stimulation and lower the temperature of the mice vaccinated fever DPT. The effective dose of ethanol extract of mangosteen peel as antipyretic analgesic is 50 mg / kg body weight.Keywords: mangosteen skin, analgesics, antipyretics